Walter the farting dog : banned from the beach - Kotzwinkle, William (Dutton Children's Books, 2007)
Although confined to a hotel room after his flatuence offends the patrons of a beach resort, Walter the farting dog makes an explosive sea rescue to save little Billy and Betty.